A multi‐hazard analysis framework for earthquake‐damaged tall buildings subject to thunderstorm downbursts. (25th January 2023) - Song, Jing; Skalomenos, Konstantinos; Martinez‐Vazquez, Pedro
Abstract: This study develops a generalised multi‐hazard analysis framework for evaluating the impact of secondary hazard events on structures that have previously been damaged by major hazardous events. More specifically, the present work investigates the effects of thunderstorm downbursts on earthquake‐damaged tall steel buildings giving an emphasis in assessing the revised accumulated earthquake‐wind ductility demands. The novel approach is validated on a 20‐storey steel building. The structure is initially subjected to a ductility‐controlled pushover analysis to simulate the earthquake‐induced damage, and then, a parametric dynamic analysis is performed using damaged structure models under synthetic downburst time‐histories developed for various wind profiles, wind velocities and terrain types. The method accurately controls the damage level induced by the primary hazard and separately assesses secondary hazard effects which enables a direct quantification of the new multi‐hazard design requirements. This can provide effective guidance in the stage of preliminary structural design or post‐hazard assessment of structures identifying new serviceability limits, as well as support repair procedures and decision‐making frameworks for existing structures to prevent collapse. The results demonstrate a significant increase up to three to four times in ductility demands of the structure after the occurrence of the strong downburst winds, compared with the ductility demands that were initially imposed by the varying severity degrees of the earthquake.